Fine structure and taxonomy of Monomorphina aenigmatica comb. nov. (Euglenophyta) - Nudelman, María A. (2006)
The euglenoid genus Monomorphina was defined by Mereschowsky in 1877 to include rigid euglenoids that were pyriform in lateral view, had a hyaline spine at the posterior end, and one to few parietal chloroplasts typically without pyrenoids. The genus included taxa previously assigned to Phacus Dujardin or Euglena Ehrenberg. The general structure of Monomorphina aenigmatica comb. nov. is described on the basis of light microscopy and scanning and transmission electron microscopy. Cells were pear-shaped in lateral view, rounded at the anterior end and narrowed posteriorly, tapering into a long twisted tail. The pellicle had helically arranged strips spiralled in a counter-clockwise fashion. A distinctive feature of M. aenigmatica was the presence of a single chloroplast bearing a pyrenoid, capped with a paramylon plate. The large parietal chloroplast extended along most of the cell with three prominent cup-shaped paramylon caps on the external face. In transverse section, the chloroplast appeared C-shaped. Because of the ambiguity surrounding the original descriptions used to diagnose this taxon, we designated an epitype for Monomorphina aenigmatica. Morphological features of this species were compared to other members of the genus.